The Relationship between Personality and Human Behavior - Akmal, Fauzi; Arifin, Zainul; Sabiruddin, Sabiruddin; Busral, Busral; Yuni, Sarah; Miagustin , Vira (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
Personality is a distinctive characteristic that distinguishes one individual from another. Personality influences how a person interacts with their environment, thinks, feels, and acts. This article aims to examine the relationship between personality and human behavior. Based on an analysis of psychological theories and previous research, it was found that dominant personality traits in an individual can influence behavioral patterns that emerge in various everyday contexts. This study outlines various personality types and their influence on social behavior, emotional adaptation, and responses to stress. The results of the study indicate that personality has a significant influence on how an individual interacts, acts, and responds to social situations.